Parent-child bonding and attachment during pregnancy and early childhood following congenital heart disease diagnosis. Issue 3 (3rd July 2022) - Tesson, Stephanie; Butow, Phyllis N.; Marshall, Kate; Fonagy, Peter; Kasparian, Nadine A.
ABSTRACT: Diagnosis and treatment of congenital heart disease (CHD) can present challenges to the developing parent-child relationship due to periods of infant hospitalization and intensive medical care, parent-infant separations, child neurodevelopmental delay and feeding problems, and significant parent and child distress and trauma. Yet, the ways in which CHD may affect the parent-child relationship are not well-understood. We systematically reviewed the evidence on parental bonding, parent-child interaction, and child attachment following CHD diagnosis, according to a pre-registered protocol (CRD42019135687). Six electronic databases were searched for English-language studies comparing a cardiac sample (i.e., expectant parents or parents and their child aged 0–5 years with CHD) with a healthy comparison group on relational outcomes. Of 22 unique studies, most used parent-report measures (73%) and yielded mixed results for parental bonding and parent-child interaction quality. Observational results also varied, although most studies (4 of 6) found difficulties in parent-child interaction on one or more affective or behavioural domains (e.g., lower maternal sensitivity, lower infant responsiveness). Research on parental-fetal bonding, father-child relationships, and child attachment behaviour was lacking. Stronger evidence is needed to determine the nature, prevalence, and predictors of relational disruptions following CHD diagnosis, and to inform targeted screening, prevention, and early intervention programs for at-risk dyads.